Russia after the Fall - Kuchins, Andrew (Book collections on Project MUSE., 2002)
Russia's first decade after the collapse of the Soviet Union has been simultaneously tumultuous and transformative. For most of the 1990s the Russian economy was in free fall, the legal system in absentia, and the majority of citizens engaged primarily in survival efforts. Not surprisingly, the former superpower also struggled to adapt to its greatly diminished means and status. Russia after the Fall is a collection of essays by internationally renowned experts on Russian politics, economics, society, and foreign and security policy. The volume is comprehensive in its coverage of key topics as well as reflective of contemporary debates on developments in Russia. The essays provide retrospective analyses on how Russia has fared in its reform efforts and a prospective look at the challenges ahead. This book will be of interest to scholars, students, and to a general audience seeking to better understand where Russia has been and where it is going. Contributors include Anders Aslund (Carnegie Endowment), Harley Balzer (Georgetown University), Clifford Gaddy (Brookings Institution), James Goldgeier (George Washington University), Rose Gottemoeller (Carnegie Endowment), Thomas E. Graham Jr. (Carnegie Endowment), Joel Hellman (World Bank), Stephen Holmes (New York University), Andrew C. Kuchins (Carnegie Endowment), Anatol Lieven (Carnegie Endowment), Michael McFaul (Carnegie Endowment), Martha Brill Olcott (Carnegie Endowment), Dmitri Trenin (Carnegie Moscow Center), and Judyth Twigg (Virginia Commonwealth University). Andrew C. Kuchins is the director of the Russian and Eurasian Program at the Carnegie Endowment where he specializes in Russian policy and security issues. He is coeditor of Russia and Japan: An Unresolved Dilemma between Distant Neighbors (Berkeley Public Policy Press, 1993).